MARKETED SURPLUS JAGUNG DAN DAMPAKNYA TERHADAP KETERSEDlAAN PANGAN NON BERAS DI PROVINSI BENGKULU - Nusril, Nusril; Andani, Apri; Nabiu, Musryadi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2010)
In general, focus of this study is to estimate non-rice food farmer market participation in Bengkulu Province in order to provide information about and variety availability of food, especially maize. Research sample areas are seven districts namely Mukomuko, North Bengkulu, Seluma, South Bengkulu, Kaur, Kepahiang, and Rejang Lebong. This research used the marketable surplus analysis, and market participation analysis to examine the availability of maize. This research found that maize has adequate potency as a substitution food. This commodity can fulfill approximately 12 percent of requirement for Bengkulu province resident. For Bengkulu farmers, maize is not an alternative food for their household members, but it has significant role for household economies. Furthermore, the research also found that maize production is able to supply energy for every Bengkulu resident approximately 244.09 kcal/capitajday. This equals to 11.90 % of energy required to conduct normal or daily activities.